The Effectiveness of Teams Games Tournament (TGT) and Make A Match Learning Models on Collaboration Ability in Science Learning - Meta-Analysis - Hendra, Yupinus; Rahayu, Theresia (Universitas Pendidikan Ganesha, 2020)
Students' low collaborative ability, so a learning model that can develop students' collaborative abilities is needed. This study aimed to analyze the TGT learning model's effectiveness and Make A Match on collaborating on the science content of fifth-grade elementary school. The type of research used in meta-analysis research. The subject of this research is the TGT learning model and Make A Match on collaboration skills. The data collection technique is by analyzing 20 articles from electronic journals through google scholar. The data analysis technique used is the effect size analysis technique. The results showed that seen from the Anacova test, the mean score of the experimental two learning model Make A Match was 66.9760 higher than the TGT learning model of 53.0370. So it can be concluded that there are significant differences in the use of the TGT learning model and Make A Match in collaboration skills. This research implies that it can be used as an alternative for teachers to develop a cooperative attitude, discuss in groups and be active in learning.